Развитие института судебного представительства в Великом княжестве Литовском - Аракелян, Минас Рамзесович; Аракелян, Мінас Рамзесовіч; Arakeljan, Minas (My University, 2009)
The article is devoted to the problem of becoming and development of institute of judicial representation on Ukrainian lands of the Grand Duchy of Lithuania. Plenary powers of judicial representative, his duties, are examined, requirement to the person, which held this position. The position of judicial representative in a trial is determined.
Аракелян М. Р. Развитие института судебного представительства в Великом княжестве Литовском / М. Р. Аракелян // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 101-109.
Keywords: институт судебного представительства; Великое княжество Литовское; судебное представительство; судебный представитель; прокурор; адвокат; судебный процесс; Статуты Великого княжества Литовского; інститут судового представництва; судове представництво; судовий представник; Статути Великого князівства Литовського; судовий процес; Institute of judicial representation; judicial representation; the judicial representative; the public prosecutor; the lawyer; Statutes of the Grand Duchy of Lithuania; trial